2019
DOI: 10.3389/fped.2019.00238
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentations and Outcomes Related to Tuberculosis in Children Younger Than 2 Years of Age in Catalonia

Abstract: Introduction: Children younger than 2 years have an increased risk of complications associated with tuberculosis (TB) due to the immaturity of the innate and adaptive immune response. We aimed to identify TB clinical presentations and outcomes as well as risk factors for complications in this age group. Materials and Methods: Multicenter, retrospective, cross-sectional study of TB cases in children aged <2 years in Catalonia (2005–2013). Epidemiological and clinical data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…In fact, adolescents are a key target group for TB control interventions, since, as stated by the WHO, adolescents are more often contagious and have a larger number of contacts in closed spaces such as schools [ 24 ]. It is also remarkable that children under 5 years of age were the only age group in which the percentage of hospitalizations exceeds that of reported cases, probably because children, especially those under 2 years of age, have more acute symptoms with more severe forms and a higher complication rate [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, adolescents are a key target group for TB control interventions, since, as stated by the WHO, adolescents are more often contagious and have a larger number of contacts in closed spaces such as schools [ 24 ]. It is also remarkable that children under 5 years of age were the only age group in which the percentage of hospitalizations exceeds that of reported cases, probably because children, especially those under 2 years of age, have more acute symptoms with more severe forms and a higher complication rate [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown a 10-15% rise in DR-EPTB [ 157 ]. EPTB is less reported in children than in pulmonary tuberculosis (PTB) [ 154 , 158 - 160 ]. It has a higher incidence of MDR-TB [ 156 , 161 ].…”
Section: Reviewmentioning
confidence: 99%
“…Hal tersebut sejalan dengan penelitian Tebandite K, dkk. ditemukan adanya anak yang sebelumnya masuk kategori BB normal mengalami penurunan BB dan masuk kategori BB kurang selama dilakukan terapi (12). Terbukti di dalam penelitian Kant S, dkk.…”
Section: Tabel 2 Hasil Pengujian Hipotesisunclassified
“…Pada penelitian Tebandite K, dkk. juga menghasilkan perbedaan statistik yang signifikan antara sebelum dan sesudah terapi OAT (12).…”
Section: Tabel 2 Hasil Pengujian Hipotesisunclassified